Ready, set, go! Mental preparation for competitions - Heinrich, A. (Journal of Biathlon Coaching, 2024)
"The physical things are difficult — using all your muscles and pumping your heart as fast as you can. [...] But the mental piece is the biggest challenge of biathlon. [...] I have this task I`ve done thousands of times that I`m trying to repeat. I know that I`m going to have distractions. The person next to me hit all of the targets. The fans are screaming. The person on the loudspeaker says, `Here`s Clare Egan from the U.S.A. Let`s see if she can hold it together.`"